Gestational anemia - Wahed, F; Latif, SA; Nessa, A; Bhuiyan, MR; Hossain, MB; Akhter, A; Mahmud, MM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):462-8 The abstract of this article is available on the PubMed website